Synthesis and characterization of new nematic liquid crystalline compounds-based thiophene units. (2nd January 2016) - Jia, Ying-Gang; Su, Dong; Guo, Zhi-Hao; Hu, Jian-She
ABSTRACT: Four new liquid crystalline thiophene compounds (M1−M4 ) with a long flexible spacer were prepared. Their structures were characterized by Fourier transform infrared and proton nuclear magnetic resonance. The mesomorphism and thermal stability were investigated with differential scanning calorimetry, polarizing optical microscopy, and thermogravimetric analysis. The photo-physical properties were evaluated using ultraviolet/visible spectroscopy and photoluminescence.M1−M4 all showed thermotropic mesogenic properties with excellent thermal stability, and exhibited nematic threaded texture, droplet texture, and Schlieren texture on heating and cooling cycles. The effect of flexible spacer and terminal groups on mesomorphic and spectroscopic property is discussed. The experimental results demonstrated that the tendency toward melting temperature (Tm ) decreased, while isotropic temperature (Ti ) increased with increasing the flexible spacer length. In CHCl3 solution, these thiophene compounds displayed an intense broad absorption band peaking within 230–340 nm and a maximum fluorescent emission wavelength at 426–439 nm.